(untitled) (Journal of history, 2025)
The article is devoted to the early history of the Ulus of Jochi. It substantiates the opinion that the modern territory of Eastern Qazaqstan, where the East Qazaqstan Region and the Abai Region are now located, and especially the pastures around the Irtysh River were the site of the foundation and location of the headquarters of Jochi Khan, the eldest son of Genghis Khan. In the 13th century, the Irtysh region constituted the main part of the possessions of the Ulus of Jochi, at first there was the camp (headquarters, horde) of Jochi himself, then the center of the ulus of the Horde, the eldest son of Jochi. Traditional methods of historical research were used, including diachronic, historical-systemic and other methods. The chronological framework of the study covers the events of the 13th century. Information from medieval written sources and scientific publications on the history and archeology of the Middle Ages is used. The range of main Muslim and European sources on the history of the Ulus of Jochi, which reflect the history of East Qazaqstan and the territory of the Abai Region, is determined. The article examines the data of Rashid al-Din, John of Plano Carpine, C. de Bridra on the events of the history of the Ulus of Jochi during the reign of Jochi, Orda and his first successors Qonghuran and Qonichi. It is suggested that the contacts of the Jochid with the Yuan Empire passed through Eastern Qazaqstan, through the Alakol Valley and the Dzungarian Gates, and the Ertis, Yesil, Tobyl rivers were the connecting threads of the northern and eastern steppes of Qazaqstan with Siberia. The history of Eastern Qazaqstan is an integral part of the socio-political, economic and cultural history of all medieval Qazaqstan. For the first time, the history of East Qazaqstan and the Abay Region is considered in the context of the history of the Ulus of Jochi, it is shown that the history of Eastern Qazaqstan is an integral part of the socio-political, economic and cultural history of medieval Qazaqstan.